(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Tolerance has a limit. Consumer movements spearheaded theattacks and slowly but surely the lobby grew stronger and stronger day by day.Awareness in a consumer, that his rights were being sabotaged, grew from day today. He realized that though on paper he was a king, nevertheless he remained aslave. The psychology under which the consumer in India had treated for decadesthat he had ‘no choice’ needed to be penetrated with an effective dose ofmaking him feel like a ‘King’ and not merely think like a ‘King.’